The Model Development of an Assessment of Nurse Educator Competencies for 21st Century among Nursing Colleges under Praboromarajchanok Institute for Health Workforce Development, Ministry of Public Health - ทองเพชร, เพ็ญศรี; จันทรา, รุ่งนภา (Nursing Journal of The Ministry of Public Health, 2019)
This research and development study aimed to 1) develop an assessment model of nurse educator competency for 21st century and 2) examine the effectiveness of the assessment model of nurse educator competency for 21st century among nursing colleges under Praboromarajchanok Institute for Health Workforce Development (PIHWD), Ministry of Public Health. The development processes included 5 phases as follow: phase 1: exploring the situation of the model of competency evaluation of nurse educator, phase 2: developing the components and indicators of nurse educator competency for 21st century, phase 3: developing an assessment model of nurse educator competency for 21st century, phase 4: evaluating the effectiveness of the model, and phase 5: confirming the model of nurse educator competency for 21st century. The data were collected using documentation review, focus group discussion, and survey questionnaire. The data were analyzed using descriptive statistics and content analysis. The results revealed that the model of the nurse educator competency assessment composed of 5 components 1) goal of the assessment is to evaluate competencies of nurse educator who work in nursing college individually according to the performance indicators that congruence with the role of nursing educators, 2) scope of the assessment is specific to the job performance including knowledge, skill, and personal attributes that necessary for job performance, 3) assessment process includes the development of assessment tool that composed of 7 components, 43 indicators, 360-degree assessor, and data collection using computer software, 4) judging the evaluation results by comparing with the assessment criteria and then create individual development plan and 5) applying the results of the assessment and monitor of an individual competency development according to competency development plan. The model of the competency assessment for nurse educator was effective. Nurse educator reported a high level of satisfaction with the assessment model. All nurse educators (100%) had been developed based on their individual development plans. The experts approved that the assessment model of nursing educator competency for 21st century was appropriate to use as a part of effective competency development of nurse educator for 21st century of nursing college under Praboromarajchanok Institute.